KLASIFIKASI EMOSI DAN EKSPRESI EMOSI PADA KLON TOKOH HANTENGU DALAM ANIME KIMETSU NO YAIBA SEASON 3 KARYA GOTOUGE KOYOHARU - I Komang Rama Kusuma; Renny Anggraeny; I Made Budiana (Cahaya Ilmu Bangsa Institute, 2025)
This research is titled “Classification of Emotions and Emotional Expressions in the Clones of Hantengu from the Anime Kimetsu no Yaiba Season 3 by Koyoharu Gotouge.” The study aims to identify the classification of emotions and emotional expressions manifested in the dialogues of the Hantengu clones in Kimetsu no Yaiba Season 3. The methodologies employed in this research are content analysis and informal methods. The theoretical framework is based on the Emotion Classification Theory and Emotion Expression Theory proposed by Robert Plutchik (1980) and Paul Ekman (1992). The findings reveal that four types of emotions are identified in the Hantengu clones: 1) Anger, 2) Happiness, 3) Pleasure, and 4) Sadness. These emotions are expressed through both verbal and non-verbal means. The results indicate that the Hantengu clones consistently express their primary emotional characteristics without alteration, both verbally and non-verbally, in accordance with the theories of emotion classification and expression put forth by Robert Plutchik and Paul Ekman.